Whole Body Vibration Exposure among the Tractor Operator during Soil Tillage Operation: An Evaluation using ISO 2631-5 Standard - Amandeep Singh; Siby Samuel; Harwinder Singh; Jagmeet Singh; Chander Prakash; Yash Kumar Dhabi (Shock and Vibration)
This study is aimed at investigating the effect of various tractor ride conditions on the lumbar spine during rotavator operation. The lumbar spinal response was assessed by determining static compressive dose, i.e., Sed (8). Raw acceleration data were measured on the seat pan and seat backrest to varying tractor velocity, tillage depth, and pulling force. The field experiments have been designed using Taguchi’s L9 orthogonal array and the entire data analyzed in signal-to-noise ratios terms. The mean acceleration responses were dominant along the vertical axis and exposure levels were found beyond the exposure action value, i.e., 0.5 m/s2 as per Directive 2002/44/EU. Mean Sed (8) exceeded the limits of ISO 2631-5 indicating the probability of adverse health effects. Tractor velocity and pulling force have a significant impact on Sed (8) with a 64.43% and 27.73% percentage contribution. The FFT dominant peaks have been found in the 0.8 to 3.7 Hz frequency range. Moreover, the exact frequency of the peaks is found to be dependent on the experimental circumstances. The depicted dominant frequencies found in the range of low frequencies could lead to musculoskeletal disorders since they coincide with the natural frequencies of various parts of the body, especially in the lumbar region.